(untitled) (Al-Qamar, 2018)
The tradition of translating the Quran into other languages dates back to the early days of Islam. Like many other eastern and western languages, Quran has long been translated into English. This article presents an introductory study of prominent English translations of the Quran. Depending on the background and perspectives of the translators, it divides these translations into three groups; Muslim’s non-Muslim’s and infidels’ translations. Giving a brief introduction of each category and introducing prominent translations concisely, it concludes that Muslims produced English translations particularly in response to the biased translations of orientalists and other non-Muslims. It ends with the suggestion that Muslim scholars should keep an eye on the new arrivals in the field to respond the new questions raised by orientalists and infidels. It also proposes an encyclopedic work on the subject.